A short review on the ultra-high temperature mechanical properties of refractory high entropy alloys - Atli, Kadri C.; Karaman, I. (Frontiers in Metals and Alloys, 2023)
Mechanical properties of refractory high entropy alloys (RHEAs) at ultra-high temperatures (> 1,100 °C) are reviewed. Deformation behavior and strengthening mechanisms of select compositions are discussed. The limited number of studies portray remarkable mechanical properties of newly developed RHEA compositions at temperatures beyond the melting point of commercial Ni-based superalloys. Yet, the lack of tensile deformation data including monotonic deformation and application relevant creep deformation data indicates RHEAs are still far from being reliable alternatives to Ni-based superalloys as high temperature structural materials. Future studies should concentrate on tensile deformation and creep of these new alloys systems at very high temperatures.